PENGARUH VARIASI PENGGUNAAN SIKAMENT LN SEBESAR 0,4% 0,6% 0,8% DAN 1% PADA PEMBUATAN BETON NORMAL - Tedi Ekki Saputra; Chrisna Djaja Mungok; Gatot Setya Budi (JeLAST : Jurnal Teknik Kelautan , PWK , Sipil, dan Tambang, 2016)
SNI 2000 is being used as a method when manufacturing the sample specimens, with cement water ratio around 0,4. The cement that being used is PCC cement with type 1 of OPC. The sample specimens are made in cylinder shaped with Æ 15 cm, and height 30 cm andbeam 60 cm x 15 cm x 15 cm. There are five variations of the sample specimens that being made, which are normal concrete, concrete + sikament LN 0,4%, concrete + sikament LN 0,6%, concrete + sikament LN 0,8%, andconcrete + sikament LN 1%. The examinations of the sample specimens are including compressive strength test, pull out test, and modulus of elasticity test, also flexural strength test. From the evaluation of the compressive strength value between the normal concrete and normal concrete with variation of sikament LN 0,4%, 0,6%, 0,8%, and 1% at 28 days, each has compressive strength value of 44,416 MPa, 45,378 MPa, 45,828 MPa, 46,110 MPa, and 46,989 MPa. The avarage values of pull out test of normal concrete and normal conrete with variation of sikament LN 0,4%, 0,6%, 0,8%, and 1% are 3,276 MPa, 3,323 MPa, 3,394 MPa, 3,677 MPa, and 3,724 MPa. Average of modulus of elasticity of normal concrete and normal conrete with variation of sikament LN 0,4%, 0,6%, 0,8%, dan 1% are 14957,007 MPa, 16853,651 MPa, 16359,308 MPa, 16624,149 MPa, and 17672,353 MPa. The flexural strength values of normal concrete and normal conrete with variation of sikament LN 0,4%, 0,6%, 0,8%, and 1% are 4,832 MPa, 4,917 MPa, 4,958 MPa, 5,048 MPa, 5,880 MPa. From the research above, the use of Sikament LN on concrete can improve the compressive strength of the characteristic of the concrete itself. Keyword: sikament ln, compressive strength, pull out, modulus of elasticity, flexural strength